Abnormal labour. Issue 3 (March 2016) - Taylor, Lynelle; Long, Audrey
Abstract: Labour is considered abnormal once it deviates from accepted rates of progress, which are dependent on the stage of labour and the parity of the partuent. The leading indication for primary caesarean section is "failure to progress" or "labour dystocia" – a blanket term that indicates an abnormal labour process, but fails to give any indication of the underlying problem. We discuss both normal and abnormal labour and have used three cases to highlight aspects of abnormal labour.